THE OVERALL DISTANCE PROVIDING OF THE SUPPORTS AND PLATFORMS FOR THE CURVES CORRECTION - Korzhenevych, I. P. (Science and Transport Progress, 2008)
Determination of the required clearance distances to the supports and platforms in the plan calculations is considered.